Application of stand-by switching large core diameter optical fiber switch - Bhuiyan, Md. Moinul Islam; Haga, Yoichi; Esashi, Masayoshi (2005)
A l x 2 optical switch using POFIPCF and an SMA coil actuator with magnetic latches is fabricated and tested. A stand-by switch using the fabricated fiber switches is assembled and its operation is confirmed.